Produção e qualidade pós-colheita do coentro (coriandrum sativum l.) em sistema orgânico e convencional - Santos, Sara Beatriz da Costa (2020)
Coriander is a vegetable used in cooking, its production can be carried out in a conventional and organic way, in which the post-harvest effects of these types of production must be observed. The objective of this study was to evaluate the productivity and post-harvest quality of coriander, produced in organic and conventional systems. The experiment was conducted in the experimental field of the Center for Human, Social and Agrarian Sciences, at the Federal University of Paraíba. The experimental design used was randomized blocks, with five treatments and six replications. The treatments were: treatment 1 (T1) control; (T2): 35 kg of N ha-1; (T3): 70 Kg of N ha-1; (T4): 105 kg of N ha-1 of organic fertilization and (T5): 70 kg of N ha-1 of conventional fertilization. It was evaluated: height, stem diameter, number of stems, mass (fresh / dry) of the part (area / root), productivity, water activity, protein, lipids, total carbohydrates, pH, water content, mineral residue, titratable acidity , soluble solids, SS / ATT ratio and bioactive compounds. The data were submitted to polynomial regression analysis, with organic fertilizer doses of: 0 (control), 35, 75 and 105 kg of N ha-1. Orthogonal Contrast tests were carried out between treatments: control, 70 kg of N ha-1 in organic and conventional systems. The conventional production system (using ammonium sulfate) promoted higher productivity and better post-harvest quality in the coriander culture. As for the organic system (using bovine manure) it should not be applied when sowing the coriander culture due to the short cycle of the species and non-mineralization of the manure during the cycle.